Promised - O'Brien, Caragh M. (New York : Roaring Brook Press, 2012)
Gaia succeeds in leading her people to Wharfton and the Enclave, but rebellion there threatens them all just when everything they have dreamed of seems to be at hand.
Keywords: Midwives -- Juvenile fiction; Sisters -- Juvenile fiction; Survival -- Juvenile fiction; Genetic engineering -- Juvenile fiction; Parents -- Juvenile fiction; Dystopias -- Juvenile fiction; Science fiction, American; Science fiction; Young adult fiction